Validity and reliability of a future-oriented critical thinking skills diagnostic test in elementary science education - Efi Kurniasari; Sugiyarto Surono; Ishafit; Selviana Veronika Moruk (Universitas Ahmad Dahlan, 2026)
Future-Oriented Critical Thinking Skills (FOCTS) extend conventional critical thinking by incorporating a future-oriented perspective that enables students to generate innovative solutions to emerging challenges. However, no validated diagnostic instrument currently exists to measure this construct among elementary school students. This study aimed to develop and evaluate the validity and reliability of a FOCTS diagnostic test for integrated science and social studies. The novelty of this study lies in operationalizing the future-oriented dimension of critical thinking into a measurable diagnostic instrument supported by both logical and face validity evidence. The subjects used involved 30 students from one elementary school. Content validity was assessed through expert judgment covering logical validity (construct alignment) and face validity (clarity, readability, and presentation), using Aiken’s V coefficient. Empirical validity was examined using Pearson’s product-moment correlation, while reliability was evaluated using Cronbach’s Alpha. Due to scheduling constraints, empirical testing involved 30 sixth-grade students from one elementary school. The results showed an overall Aiken’s V value of 0.74, indicating adequate content validity. Empirical testing revealed that 25 of the 30 items were valid r = 0.367–0.713; r-critical = 0.361, α = 0.05, while five items were invalid. The 25 valid items demonstrated high reliability Cronbach’s Alpha = 0.871. These findings indicate that the FOCTS instrument has promising psychometric properties, although further validation with larger and more representative samples is recommended before wider implementation. The findings imply that the FOCTS instrument can serve as a promising diagnostic tool for identifying elementary students’ future-oriented critical thinking strengths and needs, pending further validation with larger samples.